Uncertainty of Thermographic Temperature Measurement with an Additional close-up Lens - Dziarski, Krzysztof; Hulewicz, Arkadiusz (Measurement Science Review, 2021)
The thermographic temperature measurement is burdened with uncertainty. This non-contact temperature measurement method makes it possible to measure the temperature of the electrical device under load. When the observed object is small (a few square millimeters) the spatial resolution of the thermographic cameras is often insufficient. In this case, the use of the additional macro lens is needed. After using an additional lens, the uncertainty of the thermographic measurement is different from the uncertainty of thermographic measurement without an additional lens. The values of the uncertainty contributions depend on the conditions during the measurement and the used methodology. The authors constructed an uncertainty budget of thermographic temperature measurement with an additional macro lens, based on EA-4/02 (European Accreditation publications). The uncertainty contributions were also calculated. On the basis of the calculated values of the uncertainty contributions, it was determined which factor had the greatest impact on the value of the thermographic temperature measurement with an additional lens.